A Semantic Analysis of Metaphors Found In Ã¢â‚¬Å“Dream TheatreÃ¢â‚¬â„¢sÃ¢â‚¬Â Selected Lyrics - Ratri, Deasy Ade (LUNAR, 2017)
Metaphor is an implicit comparison in which two unlike objects are compared by identification or substitution of one for the other to suggest common quality shared by the two. It is an implied analogy in which a word or phrase is applied to a person, object, idea or concept to which it is literally or semantically inapplicable. Many students in English Department are still confused in interpreting metaphors’ meaning whereas they have learned semantics. The research aims to find the types of metaphors which are used in Dream Theatre’s selected lyrics then interpret its contextual meaning. There are five song lyrics are chosen. They are, As I am, Endless Sacrifice, Pull Me Under, The Spirit Carries On, and Through Her Eyes. This research uses theory of Chrystal that classifies the metaphors into three types. They are Conceptual Metaphor, Mixed Metaphor, and Poetic Metaphor. To achieve the research purposes, this research uses content analysis by deductive category application. The steps in deductive category application are collecting the theory related to metaphors, identifying the concepts of metaphors, coding Dream Theatre’s selected lyrics, classify the metaphors according to Chrystal theory, and interpreting the contextual meaning of metaphors. The result shows that forty three cases of metaphors which are found in Dream Theatre’s selected lyrics. There are three thirty two metaphors that included to Conceptual metaphor, Tens metaphor are Mixed metaphor, and one metaphors are Poetic metaphor. According to the result above, conceptual metaphor are higher and more often than mixed metaphor and poetic metaphor, mixed metaphor ranks second and Poetic metaphor appears as the least type Based on the result, it is suggested to the readers use the information to know widely and deeply about the types of metaphors classified by Chrystal, as the reference or study more about metaphors. For the students who are learning about metaphors or students who are in English Department are suggested to use songs in learning and improving their capability in language and interpreting the meaning. While for the lecturer, it is suggested to use songs as a resourches in teaching semantics especially in teaching metaphors